2022
DOI: 10.3390/jpm12071119
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Mucormycosis and Cancer: The Triple Threat—Hypothesis or Reality?

Abstract: COVID-19 has been responsible for widespread morbidity and mortality worldwide. Invasive mucormycosis has death rates scaling 80%. India, one of the countries hit worst by the pandemic, is also a hotbed with the highest death rates for mucormycosis. Cancer, a ubiquitously present menace, also contributes to higher case fatality rates. All three entities studied here are individual, massive healthcare threats. The danger of one disease predisposing to the other, the poor performance status of patients with all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 124 publications
(224 reference statements)
0
7
0
Order By: Relevance
“…L. corymbifera is capable of causing mucormycosis fungal infection, which can lead to ulceration of the oral cavity [ 73 , 74 ], and was recently examined to be strongly associated with mobile tongue OSCC in a recent metagenomic study examining tumour tissue against non-tumor tissue controls [ 75 ]. Lichteimia species are one of the predominant causative agents of mucormycosis in Europe, with maxillo-facial and pulmonary infections as common clinical presentations [ 76 , 77 ]. Clinical patient studies have additionally observed mucormycosis to be more commonly associated with hematological malignancies, such as acute leukemia and lymphoma, though this is possibly a result of opportunistic infection rather than tumour initiation [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…L. corymbifera is capable of causing mucormycosis fungal infection, which can lead to ulceration of the oral cavity [ 73 , 74 ], and was recently examined to be strongly associated with mobile tongue OSCC in a recent metagenomic study examining tumour tissue against non-tumor tissue controls [ 75 ]. Lichteimia species are one of the predominant causative agents of mucormycosis in Europe, with maxillo-facial and pulmonary infections as common clinical presentations [ 76 , 77 ]. Clinical patient studies have additionally observed mucormycosis to be more commonly associated with hematological malignancies, such as acute leukemia and lymphoma, though this is possibly a result of opportunistic infection rather than tumour initiation [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…These propositions are supported by decreased mortality and disease progression in large sample size of 2,826 CAROCM patients [101] . In addition to surgical procedures these guidelines recommended use of antifungal agents, for instance ICMR has recommended use of antifungal drug liposomal amphotericin B (AmB) @ 5 mg/kg/day for 4-6 weeks [101] , [132] . In case infection spread to CNS, a higher dose AmB has to be used in order to manage spread of infection and treat disease effectively and in case of non-availability of the liposomal amphotericin B, Deoxycholate and lipidcomplex of AmB has been suggested to be used in CAM patients [133] .…”
Section: Updated Guidelines For Treatments Of Cammentioning
confidence: 99%
“…Finally, anti-cancer treatments, including radiation therapy, chemotherapy, stem cell transplantation, and chimeric antigen receptor T-cell therapy, substantially elevate the risk of contracting COVID-19 due to their immunosuppressive effects. These therapies can occasionally mask prodromal symptoms like fever, potentially resulting in a delay in diagnosis [3]. Hyperinflammation and cytokine storm syndrome represent significant contributors to the development of acute respiratory distress syndrome, multiorgan failure, and ultimately, mortality in individuals infected with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%